Characterization of an in vitro persistent-state measles virus infection: species characterization and interference in the BGM/MV cell line. - Menna, J H (1975)
Serological methods of mixed agglutination and indirect immunofluorescence showed the BGM/MV cell line to possess monkey antigens. As a means of further characterizing the species constitution of the BGM/MV cell line, the species specificity of viral-induced interferon from these cells, as well as the response of these cells to exogenous interferons, was determined. Low titers of spontaneously elaborated interferon capable of protecting monkey but not mouse cells were detected in BGM/MV culture fluids. Interferon induced by Newcastle disease virus infection of BGM/MV cells was capable of conferring an antiviral state on monkey and, to a lesser extent, on mouse cells. Exogenous interferons of both homologous (BGM/MV) and heterologous sources failed to confer an antiviral state on BGM/MV cells. BGM/MV cells were found to be partially refractive to superinfection with measles virus but freely replicated mumps and vesicular stomatitis virus.